2017
DOI: 10.24170/12-2-1722
|View full text |Cite
|
Sign up to set email alerts
|

Referral pathways for reperfusion of STEMI – developing strategies for appropriate intervention

Abstract: undergo PCI within 90 minutes of FMC, should be treated with fibrinolytic therapy within 30 minutes of hospital presentation, unless such therapy is contraindicated.A recent study in STEMI patients found that while p-PCI was performed in 60%, the majority of the interventions occurred later than 120 minutes, and that only 36% received fibrinolysis.(2) This high percentage of patients receiving angiographyand an invasive treatment strategy may be explained by the location of the participating centers in urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…[1,9,10] International and local data have shown that outcomes improve when patients are referred to regional specialised centres where a multidisciplinary team may manage their ailment. [11][12][13] For this reason, many patients will require CCT.…”
Section: Discussionmentioning
confidence: 99%
“…[1,9,10] International and local data have shown that outcomes improve when patients are referred to regional specialised centres where a multidisciplinary team may manage their ailment. [11][12][13] For this reason, many patients will require CCT.…”
Section: Discussionmentioning
confidence: 99%
“…4 Locally, the majority of patients seem to be transported privately. 12 - 13 Reasons for this include unfamiliarity with emergency numbers, poor and unreliable response times of EMS, or lack of understanding of the value of EMS use in myocardial infarction. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Locally, 77% of the PCI-facilities are only accessible to 18.1% of the population. These disparities are echoed by a local study mentioning that 70% of patients in the public sector are cared for by 30% of doctors while four provinces do not have a single registered cardiologist [24] . These gaps, albeit non-significant, are illustrated in this study by a negative correlation between the amount of private cath labs and those with medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Africa is no stranger to this inequitable dissemination of resources based on socio-economic status and geographic locale [14] , [24] , [25] , [26] . Owing to the disarray of the local public transport system [27] , the high cost of travel [14] and the unreliable nature of the public EMS system [12] , [13] , even those living in close proximity to the urban concentrated PCI-facilities, might still not be able to access these in a timely manner.…”
Section: Discussionmentioning
confidence: 99%